FEDfind : your key to finding federal government information : a directory of information sources, products, and services - D'Aleo, Richard J. 1943-; Ratkus, Carol S. (Springfield, Va. : ICUC Press, 1986)
A directory of information sources and publications by or about the federal government, including private sector sources of such products or services.
Includes index.
Keywords: Government publications -- United States -- Bibliography; United States -- Politics and government -- Bibliography; United States -- Politics and government -- Bibliography; United States -- Politics and government -- Information services